Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0047817
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology of Amygdala Is Associated with Trait Anxiety

Abstract: Previous neuroimaging studies have suggested a role of amygdala in trait anxiety level, in which amygdala was typically treated as a whole. To date, it remains unknown whether the morphology of specific subregions of amygdala are associated with trait anxiety. Here, we employed a shape analysis approach to locate the association between its morphology and trait anxiety on the surface of amygdala. 24 healthy young participants were included. The boundary of amygdala for each subject was first manually outlined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…64 Posteriorly, output from the vestibuloparabrachial network 34 and amygdala-locus coeruleus pathways converge on brainstem autonomic centers. 62 Trait anxiety has been linked to the size and shape of the amygdala, 65,66 but its full expression of behavioral, psychophysiologic, and autonomic responses depend on connections with prefrontal cortex and autonomic nuclei. 36 Serotonergic and nonserotonergic projections from the dorsal raphe nucleus (not shown) to the vestibuloparabrachial network facilitate a tradeoff between instinctive motor activation and responsiveness to sensory inputs (i.e., movement versus information gathering).…”
Section: Threat Posture Locomotion and Anxiety In Health And Diseasementioning
confidence: 99%
“…64 Posteriorly, output from the vestibuloparabrachial network 34 and amygdala-locus coeruleus pathways converge on brainstem autonomic centers. 62 Trait anxiety has been linked to the size and shape of the amygdala, 65,66 but its full expression of behavioral, psychophysiologic, and autonomic responses depend on connections with prefrontal cortex and autonomic nuclei. 36 Serotonergic and nonserotonergic projections from the dorsal raphe nucleus (not shown) to the vestibuloparabrachial network facilitate a tradeoff between instinctive motor activation and responsiveness to sensory inputs (i.e., movement versus information gathering).…”
Section: Threat Posture Locomotion and Anxiety In Health And Diseasementioning
confidence: 99%
“…This hemispheric lateralization is novel and therefore it has to be interpreted with caution since no studies so far investigated the structural lateralization of the amygdala in relation to gender effects in anxiety and serotonin functions. A recent study by Li 5-HTTLPR, anxiety and gender impact on brain anatomy SCAN (2014) and colleagues (Li et al, 2012) found that the significant association between surface metrics of the amygdala and trait anxiety levels was confined to the right lateral and central nuclei, thus supporting the notion that right amygdala is in charge of reacting to negative emotion inputs. There are also studies that, investigating the biological abnormalities concomitant with impulsivity/self-aggression, described the presence of increased right amygdala volume (Spoletini et al, 2011) more evident in females (Monkul et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…In fact, anxiety-related behaviours are forms of risk assessment behaviours that are associated with a level of uncertainty or unpredictability regarding the outcome of emotionally salient events, often when both rewarding and aversive outcomes are possible. It has been proposed that these behaviours are fundamentally regulated by activity of the amygdala (Jennings et al, 2013), especially in the right side (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shape provides a significant advantage to other measures, such as volume, in that shape provides a greater acuity to detect discrete difference, thus allowing for greater discrimination (S. Li et al, 2012). This is due to the fact that while most volumetric analyses of subcortical structures look at the entire structure, shape provides an advantage in its vertex-wise approach (Voineskos et al, 2015).…”
Section: Social Cognition Factor Correlates: Hippocampus and Amygdalamentioning
confidence: 99%